Effectiveness of Using Artificial Intelligence Learning Tools and Customized Curriculum on Improving Students' Critical Thinking Skills in Indonesia - Mayasari, Nanny; Sastraatmadja , Achmad Harristhana Mauldfi; Suparman, Tarpan; Mutiara, Imas Indah; Maqfirah, Poetri AL-Viany (Eastasouth Institute, 2024)
This study investigates the effectiveness of using artificial intelligence (AI) learning tools and customized curricula in enhancing the critical thinking skills of students in Indonesia. A quantitative research design was employed, involving a sample of 250 students. Data were collected using a Likert scale ranging from 1 to 5 and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The findings indicate that all relationships between AI learning tools, customized curricula, and critical thinking skills are positive and significant. The results suggest that the integration of AI in education, combined with tailored educational content, significantly improves students' critical thinking abilities. These insights provide valuable guidance for educators and policymakers aiming to foster higher-order thinking skills in the educational system.d distance learning, guiding future studies and practical applications.n.